Incan Insights El Inca Garcilaso's Hints to Andean Readers (Translation of: Coros mestizos del Inca Garcilaso Resonancias andinas Lima, 1996 Revised and updated). - Mazzotti, José Antonio (Textos y Estudios Coloniales y de la Independencia, 2008)
Examines the "Royal Commentaries" of the Inca Garcilaso de la Vega and sets forth a new and alternative reading of this foundational text, paying close attention to the indigenous sources and Andean resonance of the work